Condições macroeconômicas e saúde - Triaca, Lívia Madeira (2018)
This thesis consists of three independent essays that seek to analyze the impact of macroeconomic conditions on the health and lifestyle of the Brazilian population. Although they are independent, the three essays are connected. The first essay aims to analyze how the macroeconomic conditions impact the health of Brazilians. To do so, a panel of aggregate data was used at state level in the period 1992-2014 and we used as proxy for macroeconomic conditions the state unemployment rate and for health different mortality rates. Previous studies that addressed this relationship pointed out some flaws in the methodology usually used in the literature, thus, we analyze this relationship through the non-parametric methodology proposed by Li, Chen and Gao (2011), which makes it possible to estimate the trends and variation coefficients in time without assuming the way these functions vary over time. The results observed for Brazil showed that the relationship between macroeconomic conditions and health changes over time. We observed a countercyclical pattern at the beginning of the period, 1992-1995, and procyclical at the end of the period, 2004-2014, for the total mortality rate. We assume that this pattern is following the country’s development. The improvements in the living conditions of the Brazilian population presented in the period 1992-2014 guided the relationship – ceasing to be countercyclical and making it pro-cyclical as the country develops. The second essay seeks to analyze the impact of macroeconomic conditions on weight measures, such as BMI, overweight, obesity and severe obesity. This essay uses the microdata of VIGITEL in the period from 2006 to 2014 and also uses the state unemployment rate as a proxy for macroeconomic conditions. The results showed that the relationship is robust and presents a procyclical pattern - increases in the unemployment rate reduce BMI, and this reduction is observed throughout the entire distribution, with statistically significant effects for measures of overweight, obesity and severe obesity. We tested two possible ways through which macroeconomic conditions may be affecting BMI, eating habits and practicing physical activities. We observed some evidence that eating habits may be guiding the relationship, but the results are inconclusive. Finally, the third essay analyzes how macroeconomic conditions influence the population's lifestyle. Again, we used VIGITEL data from 2006 to 2014 and the state unemployment rate as a proxy for macroeconomic conditions. For lifestyle we analyzed four groups: smoking, alcohol consumption, sedentary lifestyle and eating habits. This analysis aims to test whether the relationship between macroeconomic conditions and health for Brazil follows one of two hypotheses raised in the literature: hypothesis of variations in lifestyles due to opportunity cost and hypothesis of economic stress. The results found in Brazil suggest that in worse macroeconomic conditions individuals adopt harmful behaviors, such as increased smoking, consumption of fat and soft drinks, but also adopt healthy behaviors, such as reducing the consumption of alcohol and increasing consumption of fruits and vegetables. The majority of the results lead us to believe that the relationship is guided by the hypothesis of "economic stress". However, some conflicting evidence and the unavailability of information about individuals' mental health does not make it possible to validate this hypothesis.